Derecho al debido proceso del trabajador - Vinasco, Claudia Cristina (Universidad de San Buenaventura - Cali, 2017)
In the Substantive Labor Code there is no obligation for the employer to advance a procedure prior to a dismissal of a subordinate, that is, there is no guarantee of due process in favor of the worker in which he can exercise the right of defense; However, the Constitution of 1991 has to work as a fundamental right of special protection by the State, which, when harmonized with other rights of equal rank (due process and defense), it is necessary to exhaust a procedure prior to a Dismissal, as has been proclaimed by the Constitutional Court.